"The Distress is Impossible to Convey" British and German Trade-Union Reports on Labour in India (1926–1928) - Ahuja, Ravi 1961-; Sailer, Anna 1982-; Linden, Marcel van der 1952- (Work in Global and Historical Perspective, 2020)
Asian industrial competition, from Japan, China but also India, attracted greater public attention in Europe during the inter-war period than ever before. Indian industrial employment became the subject not only of extensive official enquiries, intensified legislation, a growing number of academic studies and of more popular writings, but also of debates within and between European trade unions